Dual inhibition of TMPRSS2 and Cathepsin Bprevents SARS-CoV-2 infection in iPS cells - Rina Hashimoto; Ayaka Sakamoto; Sayaka Deguchi; Renxing Yi; Emi Sano; Akitsu Hotta; Kazutoshi Takahashi; Shinya Yamanaka; Kazuo Takayama (Elsevier, 2021)
It has been reported that many receptors and proteases are required for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Although angiotensin-converting enzyme 2 (ACE2) is the most important of these receptors, little is known about the contribution of other genes. In this study, we examined the roles of neuropilin-1, basigin, transmembrane serine proteases (TMPRSSs), and cathepsins (CTSs) in SARS-CoV-2 infection using the CRISPR interference system and ACE2-expressing human induced pluripotent stem (iPS) cells. Double knockdown of TMPRSS2 and cathepsin B (CTSB) reduced the viral load to 0.036% ± 0.021%. Consistently, the combination of the CTPB inhibitor CA-074 methyl ester and the TMPRSS2 inhibitor camostat reduced the viral load to 0.0078% ± 0.0057%. This result was confirmed using four SARS-CoV-2 variants (B.1.3, B.1.1.7, B.1.351, and B.1.1.248). The simultaneous use of these two drugs reduced viral load to less than 0.01% in both female and male iPS cells. These findings suggest that compounds targeting TMPRSS2 and CTSB exhibit highly efficient antiviral effects independent of gender and SARS-CoV-2 variant.